Cancer cell killing by target antigen engagement with engineered complementary intracellular antibody single domains fused to pro-caspase3 - Chambers, J; Brend, T; Rabbitts, T (Nature Research, 2019)
Many tumour causing proteins, such as those expressed after chromosomal translocations or from point mutations, are intracellular and are not enzymes per se amenable to conventional drug targeting. We previously demonstrated an approach (Antibody-antigen Interaction Dependent Apoptosis (AIDA)) whereby a single anti-β-galactosidase intracellular single chain Fv antibody fragment, fused to inactive procaspase-3, induced auto-activation of caspase-3 after binding to the tetrameric β-galactosidase protein. We now demonstrate that co-expressing an anti-RAS heavy chain single VH domain, that binds to mutant RAS several thousand times more strongly than to wild type RAS, with a complementary light chain VL domain, caused programmed cell death (PCD) in mutant RAS expressing cells when each variable region is fused to procaspase-3. The effect requires binding of both anti-RAS variable region fragments and is RAS-specific, producing a tri-molecular complex that auto-activates the caspase pathway leading to cell death. AIDA can be generally applicable for any target protein inside cells by involving appropriate pairs of antigen-specific intracellular antibodies.